Personality Types in Relation to the Periodontal Health Status and Salivary Dehydroepiandrosterone among Teachers in Baghdad City - Al-Dafaai, Raya Rashid; Diab, Ban Sahib; Abd Al- Ghani, Huda Abd Al- Ghani Jameel (Journal of Baghdad College of Dentistry, 2016)
Background: The individual differences in emotional and behavioral style can be examined through personality instruments. These differences may explain the health status of the individuals. The purpose of the present study was to assess the influence of Personality Types on gingival and periodontal health status among teachers in Baghdad city in relation to selected salivary hormone (Dehydroepiandrosterone).Materials and methods: Females teachers 534 of randomly selected schools were subjected to personality questionnaire using The Riso-Hudson Enneagram Type Indicator. Teachers were examined to estimate the periodontal status according to the Community Periodontal Index (CPI). A group of teachers were selected for salivary analysis of Dehydroepiandrosterone (DHEA).Results: Data analysis showed that the higher mean of scores was reported for the Helper personality Type among the sample. According to the maximum (CPI) code, significant difference was found in the mean values of Individualist Personality Type scores between the healthy periodontium (code 0) and calculus (code 2) of Community periodontal index. No significant correlation was found between salivary DHEA concentration (pg /ml) and the scores of the Nine Personality Types. No significant correlation was found between salivary DHEA concentration(pg/ml) and number of sextants for CPI codes. Conclusions: Personality Types could influence gingival and periodontal health status of the subjectsso that psychological interventions may be carried out to improve the oral hygiene condition of the population.